2020
DOI: 10.1007/s15010-020-01482-9
|View full text |Cite
|
Sign up to set email alerts
|

Bloodstream infection due to Enterobacter ludwigii, correlating with massive aggregation on the surface of a central venous catheter

Abstract: We report a case of catheter associated bloodstream infection due to Enterobacter ludwigii with a massive aggregation on the outside surface of a central venous catheter (CVC). The 57 years old patient with a history of spondylodiscitis and Staphylococcus aureus-associated endocarditis was admitted to the intensive care unit for acute cerebral infarction. The patient developed signs of infections and the CVC was removed 11 days after placement. The infectious agent was identified by standard diagnostics to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Members of ECC are increasingly isolated as hospital-acquired pathogens 17 . Enterobacter ludwigii and other members of the ECC complex are also known to cause a range of life-threatening infections, including catheterassociated urinary tract infections, bacteremia, and surgical site infections, and have the capacity for acquiring resistance genes, as previously reported by other authors 18,19,20 . This makes the isolation of E. ludwigii (in this study) significant, as it constitutes a potential threat, mainly because of its drug resistance pattern.…”
Section: Resultsmentioning
confidence: 60%
“…Members of ECC are increasingly isolated as hospital-acquired pathogens 17 . Enterobacter ludwigii and other members of the ECC complex are also known to cause a range of life-threatening infections, including catheterassociated urinary tract infections, bacteremia, and surgical site infections, and have the capacity for acquiring resistance genes, as previously reported by other authors 18,19,20 . This makes the isolation of E. ludwigii (in this study) significant, as it constitutes a potential threat, mainly because of its drug resistance pattern.…”
Section: Resultsmentioning
confidence: 60%
“…Total coliforms were also isolated from the ET-1 sediment samples as well as from RG at wk4 and STa at wk5, during the FCC; and from RG at wk7 and RW at wk8, which was also E. coli positive, after the FCC (Fig 4). Table 1 shows the taxonomic identification of the six total coliform isolates which were identified as Stenotrophomonas maltophilia (from STa), Raoultella planticola (from STa and RG), two members of the Enterobacter cloacae complex, E. ludwigii and E. hormaechei (from ET-1 and RW, respectively), and Acinetobacter johnsonii (from RG), all of which have been associated with human infections and are considered opportunistic pathogens [56][57][58][59][60]. Due to the sporadic detection of total coliforms and E. coli at the various locations during this study, the positives detected may have been a result of their temporal and spatial proximity to boil advisory issuing events and not related to the FCC.…”
Section: Discussionmentioning
confidence: 99%
“…Few bacterial species dominated the profile of pathogenic bacteria in biofilm samples; the seven most abundant pathogenic bacteria already represented over 80% of the 69 identified pathogenic bacteria in biofilm samples. E. ludwigii has been recently identified in a case of catheter-associated bloodstream infection with massive aggregation of the bacterium outside the central venous catheter ( Wagner et al, 2020 ). Other pathogens have also been reported as colonizers of PE and PP ( A. hydrophila : Thomas et al, 2020 ), as possible degraders of LDPE and as microplastic surface colonizers ( N. farcinica : Soleimani et al, 2021 ; Yi et al, 2021 ), or were identified as so-called ultramicrocells from drinking water systems made of PVC pipes ( Afipia sp.…”
Section: Discussionmentioning
confidence: 99%